2020
DOI: 10.1177/0300060520939832
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-dose ColchiciNe on the InciDence of Atrial Fibrillation in Open Heart Surgery Patients: END-AF Low Dose Trial

Abstract: Background Studies using 1 mg of colchicine to prevent postoperative atrial fibrillation (POAF) reported conflicting results. Moreover, colchicine was associated with significant gastrointestinal (GI) side effects. This study examined whether low-dose colchicine effectively prevents POAF and whether low-dose therapy is associated with lower rates of colchicine-induced GI side effects. Methods In this prospective, randomized, double-blind, placebo-controlled study, consecutive adult patients admitted for electi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…A statistically significant difference was discovered only for the frequency of diarrhea occurrence in the early postoperative period. This indicator was higher in the treatment group (16 (32%) patients) than in the control group (6 (11.8%) patients), which was consistent with available published data on the negative effect of colchicine on the digestive tract [ 6 , 7 , 10 , 19 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A statistically significant difference was discovered only for the frequency of diarrhea occurrence in the early postoperative period. This indicator was higher in the treatment group (16 (32%) patients) than in the control group (6 (11.8%) patients), which was consistent with available published data on the negative effect of colchicine on the digestive tract [ 6 , 7 , 10 , 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the outcomes of research on the efficacy of colchicine are ambiguous and require further investigation [ 18 , 19 , 20 ]. In this regard, the objective of our study was to evaluate the efficacy of short-term colchicine administration in terms of preventing POAF in patients after open-heart surgery.…”
Section: Introductionmentioning
confidence: 99%
“…independently reviewed the 149 identified articles. Finally, we included 9 RCTs that evaluated the efficacy of colchicine in preventing atrial fibrillation after cardiothoracic surgery or cardiac intervention [15][16][17][18][19][20][21][22][23].…”
Section: Search Strategy and Inclusion Criteriamentioning
confidence: 99%
“…One hundred and forty-nine articles were identified, and 9 possibly pertinent articles were chosen after a primary search. Nine studies involving 2031 patients were finally included in our analysis [15][16][17][18][19][20][21][22][23] (Fig. 1).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…However, a recent randomized controlled trial (1 mg of colchicine 24 h before the surgery, as well as on days 2, 3, 4, and 5 in the postoperative period) did not detect any statistically significant differences between the control and colchicine groups within 7 days after surgery (Shvartz et al, 2022). Two other studies also found similar results (Bessissow et al, 2018;Tabbalat et al, 2020). Although the above-mentioned opposite outcomes may be attributed to the small sample size and early study termination, the effectiveness of colchicine in preventing AF needs to re-examination.…”
Section: Therapeutic Potential Of Targeting Immune Remodelingmentioning
confidence: 91%